22q11.2 Deletion Syndrome–Associated Parkinson's Disease. Issue 1 (9th November 2018) - Boot, Erik; Bassett, Anne S.; Marras, Connie
Abstract: Background: 22q11.2 deletion syndrome (22q11.2DS) is a multisystem condition associated with an increased risk of early‐onset Parkinson's disease (PD). Methods: We review the clinical, neuroimaging, and neuropathological observations, as well as diagnostic challenges, of PD in 22q11.2DS. We conducted a search of PubMed up until June 1, 2018 and personal files to identify relevant publications. Results: 22q11.2DS‐associated PD is responsible for approximately 0.5% of early‐onset PD. The hallmark motor symptoms and neuropathology of PD, and typical findings of reduced striatal dopamine transporter binding with molecular imaging, are present in 22q11.2DS‐associated PD. Mean age at PD onset in 22q11.2DS is relatively young (∼40 years). Patients with 22q11.2DS‐associated PD show a good response to levodopa. Conclusions: Further recognition of 22q11.2DS and study of PD in people with 22q11.2DS could provide insights into the mechanisms that cause PD in the general population. 22q11.2DS may serve as an identifiable PD model to study prodromal PD and disease‐modifying treatments.